Stabilization of systems with switchings on the axis of their coordinates and its input-to-state properties. (May 2019) - Aparicio, Andrea; Fridman, Leonid; Efimov, Denis
Abstract: The stabilization problem for switched systems in which switchings occur on the axes of its state coordinates is considered. It is shown that a linear feedback, or a combination of linear feedback and a switching law, can be designed such that the closed-loop is stable, and has the input-to-state property, allowing to guarantee robustness against matched and unmatched perturbations. The conditions of stability are expressed in the form of linear matrix inequalities. The results are illustrated by numerical simulations.